Pengaruh Persepsi Customer Satisfaction dan Kepercayaan Konsumen Terhadap Intensitas Minat Menggunakan Layanan Dompet Digital (Shopeepay) Pada Masyarakat di Kota Medan - Nibra, Bagas Elwi; Siregar, Onan Marakali (Peneliti.net, 2025)
The advancement of digital technology has changed the lifestyle of the people of Medan City. People's lives are now highly dependent on smartphones and the internet. This has encouraged the development of digital technology-based financial services, also known as fintech. ShopeePay is one of the most widely used and interested fintechs in the community. Customer satisfaction and consumer trust are factors that attract people to use ShopeePay. However, there are still complaints from ShopeePay users regarding customer satisfaction and consumer trust. This study aims to determine the effect of customer satisfaction and consumer trust on interest in using. The form of research used is quantitative with an associative approach. The population in this study were people who used ShopeePay digital wallet services in Medan City, with a sample of 96 respondents, with the sampling technique using purposive sampling. The analysis techniques used are instrument tests, classical assumption tests, multiple linear regression analyses, partial tests, simultaneous tests, and determination coefficient tests. The results of this study indicate that customer satisfaction and consumer confidence have a significant positive effect on interest in using, and have an effect of 54%, while the remaining 46% is influenced by other factors outside this research model.